The impact of digital leadership in the effectiveness of organizational crisis management by mediating strategic vigilance - Hassan, Noor Kareem; Hamed, Suhair Adel (Journal of Economics and Administrative Sciences, 2022)
The current research aims to verify the impact of digital leadership as an independent variable, in the effectiveness of crisis management as a response variable through centralizing strategic vigilance in the faculties of the University of Baghdad and its departments, and to investigate the level of interest of its leaders and subordinates in research variables, as well as coming up with recommendations that contribute to strengthening the practices of the three variables. In the university under study, and based on the researcher’s interest to diagnose the influence relationship between the variables, because of their importance in the university’s headquarters and its members on the one hand, and its reflection on society on the other hand, the descriptive exploratory approach was adopted in completing the chapters and sections of the current research, as the research community included university colleges Baghdad, consisting of (24) colleges, the researcher targeted a sample of (160) views that included(Dean, Associate Dean, Head of Department)By adopting the questionnaire that included (57) paragraphs, personal interviews, and field inspection to enhance the practical aspect, while the researcher used statistical programs